Expression of PD-L1 in Lung Carcinoma and Its Correlation with Histopathological Grade, Stage, and Survival of Patients - Dhawan, Vishesh; Chandra, Smita; Kala, Mansi; Khanduri, Sushant (Journal of Laboratory Physicians, 2022)
Objective PD-L1, a 40 kDa type 1 transmembrane protein, suppresses the adaptive arm of the immune system. The interaction of PD-1 with the ligand PD-L1 inhibits cytokine production and plays a role in the progression of lung cancer. The present study was performed to observe the expression of PD-L1 in lung carcinoma patients and its correlation with histopathological grade, stage, and survival of patients.Materials and Methods This prospective study included all new cases of lung carcinoma diagnosed on histopathological or cytopathological examination over a period of 1 year. PD-L1 immunoexpression was statistically analyzed and graded according to the Tumor Proportion Score in all cases and correlated with histopathological grade, stage, and survival of patients.Results This study included 56 cases of lung carcinoma with 64.2% cases showing PD-L1 positivity, out of which 44.6% were non-small cell and 19.6% were small cell lung carcinoma. In all, 32.1% cases with lymphovascular invasion, 53.5% with necrosis, and 37.5% cases with greater than 5/10 HPF mitotic figures showed positive PD-L1 expression. Paired cell blocks and histopathology showed 70% concordance for PD-L1 expression. 16.1% cT3N1M0 cases and 25% stage IIIA cases showed PD-L1 positivity. In all, 60.7% patients with positive PD-L1 expression did not survive for 12 months following diagnosis.Conclusion PD-L1 immunoexpression was increased in lung carcinoma cases and was associated with poor histomorphological features including lymphovascular invasion, necrosis, and increased mitotic activity. PD-L1 correlated with cases having decreased 12-month survival and stage IIIA carcinoma. Thus, it may be useful in the stratification of patients who benefit from the PD-L1 targeted therapy.
Keywords: programmed death ligand-1; lung carcinoma; histopathological grade